A place in the sun? Discursive constructions of positive outcomes in post-migration stories in the Algarve - Torkington, Kate (2020)
This study argues for more comparative research between seemingly different migrant groups, bringing a new focus on intra-European migration in Portugal by examining and comparing the reasons why migrants from different geographical origins choose to settle in the tourism-based Algarve region. Drawing on data collected from a questionnaire survey and interviews, the study first compares the profiles of two apparently distinct migrant groups - Northern and Eastern Europeans - and goes on to explore their discursive representations of migration experiences. Findings reveal that despite differences in initial motivations for moving to the Algarve, there are similarities between the two groups in terms of what leads them to settle in the region. Among both groups there is a high level of positive place-identity, suggesting that the specific context of the destination place plays a significant role in positive post-migration outcomes, something which is often overlooked in migration studies. Furthermore, the lived and perceived lifestyle affordances of the destination place, especially when discursively compared with the place and lifestyle left behind, are flagged by both groups and lend support to the idea that the role of lifestyle in migration has a wider significance than is usually credited.